2013
DOI: 10.1002/psc.2540
|View full text |Cite
|
Sign up to set email alerts
|

Design of NK‐2‐derived peptides with improved activity against equine sarcoid cells

Abstract: Equine sarcoid is a topically accessible model for the evaluation of anticancer peptides acting by physical membrane disruption avoiding the complexity of a systemic application. We aim at evaluating and improving natural peptides for host defence as lead structures, where we focus on the cationic and amphipathic peptide NK-2. Cytotoxicity tests, fluorescence microscopy and a chip-based biosensor, which enabled real-time monitoring of cell metabolism, were applied. Cancer cell killing was dynamic with an initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 51 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…Peptides (C7A, C7A-D21K, C7A-Δ), and NK11 used in this study were based on NK-2 (Table 2 and [17]). The most basic modification entailed replacement of the non-functional sole Cys7 residue within the NK-2 sequence with an Ala residue (C7A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Peptides (C7A, C7A-D21K, C7A-Δ), and NK11 used in this study were based on NK-2 (Table 2 and [17]). The most basic modification entailed replacement of the non-functional sole Cys7 residue within the NK-2 sequence with an Ala residue (C7A).…”
Section: Resultsmentioning
confidence: 99%
“…The most basic modification entailed replacement of the non-functional sole Cys7 residue within the NK-2 sequence with an Ala residue (C7A). This substitution has been shown to improve anti-cancer cell activity of the lead structure NK-2 [17]. An enhancement of C7A's positive net charge was achieved by substituting Asp21 by a Lys residue (C7A-D21K).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such mechanisms would have likewise impeded the activity of any peptide tested here, which in fact was not observed. Instead, based on recent and previous findings , it may be concluded that the cysteine‐to‐alanine substitution at position 7 was key to the sustained activity in medium, most likely via reducing the risk of side chain oxidation, thus, enhancing peptide stability.…”
Section: Discussionmentioning
confidence: 99%